Finlay donovan is killing it eaudiobook - Cosimano, Elle (Finlay Donovan, 2021)
"Angela Dawe's narration makes YA author Elle Cosimano's debut novel for grown-ups a wild and funny romp...Dawe offers Cosimano's laugh-out-loud moments with just the right sparkle." — AudioFile Magazine IT'S MURDER BEING A HIT-MOM "Getting the job done" for one single mom takes on a whole new meaning in Finlay Donovan is Killing It , a deliciously witty adult debut—the first in a brilliant new series from YA Edgar Award nominee Elle Cosimano. FINLAY DONOVAN IS KILLING IT . . . except, she's really not. The new book she promised her literary agent isn't written, her ex-husband fired the nanny without telling her, and this morning she had to send her four-year-old to school with hair duct-taped to her head. When Finlay's overheard discussing the plot of her new novel with her agent over lunch, she's mistaken for a contract killer and inadvertently accepts an offer to dispose of a problem husband in order to make ends meet . . . and she soon discovers that crime in real life is a lot more difficult than its fictional counterpart. A Macmillan Audio production from Minotaur Books